Psoriasis as a risk factor of pulmonary embolism – case report - Milić, Rade T; Šarac, Sanja B; Lazović-Popović, Biljana; Dinić, Miroslav (Vojnosanitetski pregled, 2021)
Abstract Introduction. Deep vein thrombosis and pulmonary embolism, known as venous thromboembolism, constitute a major global burden of disease. Both entities share the same risk factors. Psoriasis is a common, chronic skin disease. It also presents multisystemic inflammation, mainly affecting skin and joints, but it is also associated with the significant cardiovascular and metabolic states and comorbidities, on the so-called “psoriatic march”. Case report. We presented a 78-year-old female patient, with psoriasis associated with pulmonary embolism which is accidentally discovered. We did not find any other predisposing factor of this disease (primary or secondary thrombophilia), except hyperhomocysteinemia. The patient was treated with low molecular weight heparin (enoxaparin), followed by the administration of an oral vitamin K antagonist (warfarin sodium) in the weight adjusted regimens. Additionally, we recommended vitamin B complex, including folate. Supposed link between hyperhomocysteinemia and psoriasis was the decreased serum folate level as the result of increased vitamin utilization in the skin because of increased DNA synthesis. Conclusion. The reported case reflects existing literary knowledge about the increased risk of VTE and arterial thromboembolic events in the psoriatic patients. The highest risk appears in the patients with a severe disease and may be a consequence of systemic inflammation and hyperhomocysteinemia.